PENINGKATAN PENGENDALIAN KUALITAS UNTUK MENURUNKAN REJECT PADA PRODUK COPPER BUSBAR DENGAN METODE QUALITY CONTROL CIRCLE (QCC) DAN FAILURE MODE EFFECT ANALYSIS (FMEA) DI PT. XYZ - pratama, Gilang ardi; Khasbunalloh; Kurniasih, Nia (Universitas Pamulang, 2025)
Sutrakabel Intimandiri is a company operating in the cable and copper industry. One of the products is copper busbar products. In copper busbar production, there is an obstacle in the form of a reject rate that exceeds the company's target ratio. Based on these problems, the methods used are Quality Control Circle (QCC) and Failure Mode Effect Analysis (FMEA) which aims to find factors that cause rejects in copper busbars. The results of the QCC and FMEA methods show the same high Pareto numbers, namely in the QCC method there are 7056 reject bubbles with a percentage of 43% and in the FMEA method there are 112 RPN reject bubble values with a percentage of 52.3%. In this analysis, looking for factors that cause reject bubbles is assisted by using fishbone with the 4M1E factor and improvements using the 5W1H method. The proposed improvements are to emphasize information related to SOPs strictly during daily briefings to reprimand workers if they still do not follow the SOPs, stricter supervision from the Unit Head by asking the relevant operator whether there are any problems currently occurring during the process, emphasizing the system. Autonomous Maintenance, implementing a checksheet for checking the quality of dies, revising the standard process by adding a water setting item to the manufacturing specification document, even though the manual provides the steps to be carried out, holding a machine and control checksheet every 30 minutes, the Section Head submitted a request to repair the roof which was already worn out. Keywords: Quality, QCC, FMEA, fishbone, 5W1H